Homenaje a hobart m. smith a sus 100 años de vida: colecciones digitales en el repositorio ciencias, Facultad de Ciencias, UNAM - Michán, Layla; Fernández y Fernández, Daniela (Instituto de Ecología, A.C., 2012)
Hobart M. Smith is one of the most important and renowned herpetologist of all times, he is considered an expert of the herpetofauna of Mexico. In 2006 he donated his personal literature collection to the Universidad Nacional Autónoma de México (UNAM). The 100th anniversary of his birth was on September 26th, 2012, so the Science Faculty Repository, UNAM celebrated this special daywith the inauguration of the Digital Center of Herpetological Information by Oscar Flores Villela. This facility contains the catalogue of the Hobart M Smith’s library, images and the records and the Synopsis of the herpetofauna of Mexico, the information center is available in the Repository Ciencias, UNAM <http://repositorio.fciencias.unam.mx:8080/xmlui/handle/123456789/43326>.